Drug Design for Alzheimer’s Disease: Biologics vs. Small Molecules - Weaver, Donald F. (Current Alzheimer Research, 2023)
There shall probably be no “magic bullet” for Alzheimer’s; rather, we should be pursuing a “magic shotgun blast” that will target multiple complementary therapeutic receptors. Although protein misfolding/oligomerization will probably be one of these targets, this alone is insufficient and will require the co-administration of other therapeutic entities engaging targets, such as immunopathy, gliopathy, mitochondriopathy, synaptotoxicity or others. Although polypharmacy is emerging as the preferred therapeutic route, many questions remain unanswered. Should this be a cocktail of biologics, a concoction of small molecules, or a judicious combination of both? Biologics and small molecule drugs display both strengths and weaknesses. When addressing a disease as complex and globally important as Alzheimer’s, there should be room for the continuing development of both of these therapeutic classes. Each has much to offer, and when used with their advantages and disadvantages in clear focus, an ultimate solution will probably require contributions from both.
Keywords: small molecule drugs